2020
DOI: 10.1186/s12891-020-03769-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of suprascapular notch and scapular dimensions in Ugandan dry scapulae with specific reference to the incidence of completely ossified superior transverse scapular ligament

Abstract: Background Understanding of suprascapular notch (SSN) anatomy and relationship with scapular dimensions are vital in diagnosis, prevention, and assessment of suprascapular nerve entrapment syndrome. The study aimed to assess morphometry of suprascapular notch and scapular dimensions in Ugandan dry scapulae with specific reference to scapulae with completely ossified superior transverse scapular ligaments. Methods This was a cross-sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…No suprascapular notch was found in 9.1% of the studied scapulae with near results in American (1) and Greek (13) populations; while it was 24.2 %,22%, and 21.4% in Polish (14), Kenyan (12), and Italian (16) populations respectively. It was revealed that the incidence of the suprascapular foramen was different in different populations.…”
Section: Discussionmentioning
confidence: 67%
“…No suprascapular notch was found in 9.1% of the studied scapulae with near results in American (1) and Greek (13) populations; while it was 24.2 %,22%, and 21.4% in Polish (14), Kenyan (12), and Italian (16) populations respectively. It was revealed that the incidence of the suprascapular foramen was different in different populations.…”
Section: Discussionmentioning
confidence: 67%
“…Updated morphological and morphometrical data on the suprascapular region help clinicians and surgeons in the diagnosis and treatment of suprascapular neuropathies and decompression of SN [ 13 ]. Suprascapular nerve entrapment syndrome was commonly reported in the sport persons who excessively abduct and lateral rotate the upper limbs such as volleyball, tennis players and weight lifting [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morphology and morphometric dimensions of SSN in one country could not be used as a standard reference for other locations, where the race, genetic structure, environmental difference and geographic nature were considered as population specific factors responsible for the variations across the populations [ 13 , 15 , 16 ]. The morphological variations of SSN were considered as one of the predisposing factors to SNES, mainly the narrow or V-shaped SSN [ 8 , 13 , 16 ], where excessive rotation and abduction of the upper limbs could induce marked kinking with subsequent irritation, microtrauma, injury and entrapment of SN. Such effect was described as the sling effect of SSN on SN [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although variations in the SSN have been reported between individuals [1, 3, 5, 7, 17, 22, 25, 39], the differences between the right and left SSN in the same individual are unknown. Moreover, the clinical features associated with an ossified STSL are unknown other than age, which has been reported as a factor related to ossified STSL [17, 39].…”
Section: Introductionmentioning
confidence: 99%